(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2024)
Design and analysis of optimisation protocols used for performance enhancement of machining based components manufacturing is currently an active area of machining science. This experimental investigation research deals with determining and optimising the effects of three input parameter metrics on the performance realisation of good surface quality output and energy consumption during the dry machining process of EN 24 steel material by turning on the CNC lathe. The input parameter metrics considered were cutting speed, depth of cut and feed rate. The study, employed Taguchi full factorial design approach in planning the experimental process and estimate the effects of the input metrics on the response; three phase digital energy meter to capture electrical power consumption data online; offline recorded surface roughness data and used Minitab 18 statistical software analysis of variance to assess the influence of cutting parameters on the response parameters, and the Signal to noise ratio main effects plot as the optimisation tool for the various response parameters. The paper aimed to determine the appropriate cutting parameter settings required on the lathe machine in order to produce EN 24 components of better surface quality at minimum energy expenditure. The experimental data analysis results established the optimum operating conditions at varied cutting parameter settings with respect to the different response parameters and the results were presented for the surface roughness, material removal rate and specific cutting energy use.